Impacting Pre-Service Teachers Sociocultural Awareness, Content Knowledge and Understanding of Teaching ELLs Through Service-Learning - Hutchinson, Mary C. (International Journal of Research on Service-Learning in Teacher Education, 2011)
Preparing teachers to work with English language learners (ELLs) is of critical importance given their increased numbers in schools. One promising initiative is the subject of this study: combining ESL coursework with a service-learning component in a teacher education program. This research explores the impact of this service-learning initiative on pre-service teachers sociocultural awareness, content knowledge and understanding of teaching ELLs.